(untitled) (Journal of Civil Engineering Researchers, 2022)
The subject of evaluating the vulnerability and strengthening of structures against various natural and artificial factors such as earthquake, wind, fire and explosion, etc., has been the focus of most civil engineering researchers in recent years. However, the engineering profession is generally not well aware of the design of static or dynamic structures to resist the explosion. In this research, it has been done by presenting materials about the introduction of explosion and the components of this type of loading, and by examining the parameters in explosive loading and the relationship between them, Review and presentation of comprehensive information in this regard has been discussed.